2003
DOI: 10.1109/tc.2003.1228515
|View full text |Cite
|
Sign up to set email alerts
|

Random redundant storage in disk arrays: Complexity of retrieval problems

Abstract: Random redundant data storage strategies have proven to be a good choice for efficient data storage in multimedia servers. These strategies lead to a retrieval problem in which it is decided for each requested data block which disk to use for its retrieval. In this paper, we give a complexity classification of retrieval problems for random redundant storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…|M j | = 2 for all j. However, for that case we can prove by a reduction from a special form of satisÿability [17] that the problem remains NP-complete in the strong sense [13].…”
Section: Time-based Load Balancingmentioning
confidence: 96%
See 1 more Smart Citation
“…|M j | = 2 for all j. However, for that case we can prove by a reduction from a special form of satisÿability [17] that the problem remains NP-complete in the strong sense [13].…”
Section: Time-based Load Balancingmentioning
confidence: 96%
“…We use the fact that all arcs, except for the arcs from the source and the arcs to the sink, are directed from the edge nodes to the disk nodes and that the maximum ow is at most n, such that an algorithm for BRP can be constructed with a time complexity of O(mn log n) [13], where the log n part comes from a bisection search over values of K.…”
Section: Block-based Load Balancingmentioning
confidence: 99%
“…The proof is by reduction from the strongly NP-hard scheduling problem P |M j |C max ≤ 2 [3]. According to the notation for machine scheduling problems [4], problem P |M j |C max ≤ 2 can be described as follows.…”
Section: Problem Complexitymentioning
confidence: 99%
“…Dawande et al [4] showed a combinatorial 2-approximation algorithm for the restricted case of the MK-AR where the size of an item is equal to its profit. Approximation algorithms for other restricted instances of the MK-AR have been studied as well [1,2].…”
Section: Introductionmentioning
confidence: 99%